Boundedness of multilinear singular integral operators on the homogeneous Morrey–Herz spaces - Wu, Jianglong (Ukrains’kyi Matematychnyi Zhurnal, 2009)
A boundedness result is established for multilinear singular integral operators on the homogeneous Morrey–Herz spaces. As applications, two corollaries about interesting cases of the boundedness of the considered operators on the homogeneous Morrey–Herz spaces are obtained.